Vì a+b+c=0 nên \(\left\{{}\begin{matrix}a=-\left(b+c\right)\\b=-\left(c+a\right)\\c=-\left(a+b\right)\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}a^2=\left(b+c\right)^2\\b^2=\left(c+a\right)^2\\c^2=\left(a+b\right)^2\end{matrix}\right.\).Thay vào P được : \(P=\frac{a^2}{2bc}+\frac{b^2}{2ac}+\frac{c^2}{2ab}\)
\(\Leftrightarrow P=\frac{1}{2}\left(\frac{a^3+b^3+c^3}{abc}\right)\)
.Ta có đẳng thức sau \(a^3+b^3+c^3-3ab=\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=0\Rightarrow a^3+b^3+c^3=3abc\)
Thay vào P đc \(P=\frac{1}{2}.3=\frac{3}{2}\).Đẳng thức trên chứng minh rất dễ
Từ $a+b+c=0 \Rightarrow b+c=-a \Rightarrow (b+c)^2=(-a)^2 (*)$
$\Rightarrow b^2+2bc+c^2=a^2 \Rightarrow a^2-b^2-c^2=2bc$
Tương tự $b^2-c^2-a^2=2ca,c^2-a^2-b^2=2ab$
Mặt khác từ $(*)$ $\Rightarrow b^3+3bc(b+c)+c^3=-a^3 \Rightarrow a^3+b^3+c^3=-3bc(b+c) \Rightarrow a^3+b^3+c^3=3abc$
Do vậy \(\dfrac{{{a^2}}}{{{a^2} - {b^2} - {c^2}}} + \dfrac{{{b^2}}}{{{b^2} - {c^2} - {a^2}}} + \dfrac{{{c^2}}}{{{c^2} - {a^2} - {b^2}}}\)
\( = \dfrac{{{a^2}}}{{2bc}} + \dfrac{{{b^2}}}{{2ca}} + \dfrac{{{c^2}}}{{2ab}} = \dfrac{{{a^3} + {b^3} + {c^3}}}{{2abc}} = \dfrac{{3abc}}{{2abc}} = \dfrac{3}{2}\)